Evaluasi Kebijakan Pengelolaan Dana Desa: Studi Kasus di Desa Keliobar Kabupaten Kepulauan Tanimbar - Alaslan, Amtai (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the policy evaluation of Village Fund management in Keliobar Village, Tanimbar Islands Regency. The focus of this research includes the evaluation of Village Fund management based on six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This is a qualitative descriptive study, with primary data sources consisting of key informants such as the Village Secretary and supporting informants including village government officials and local community members. Data were collected through observation, interviews, and documentation. The data analysis technique used was the interactive model, consisting of data collection, data condensation, data display, and conclusion drawing. The findings indicate that the evaluation of Village Fund management in Keliobar has generally complied with applicable regulations and is functioning relatively well, although several challenges remain. The management of the Village Fund is aimed at the public interest and is realized through tangible forms such as infrastructure development. Accountability is considered good, although there are still obstacles on the part of the village government, particularly in terms of limited human resources and a lack of understanding in program planning.